Clinical insights into the role of bepridil in recurrence prevention after ablation of persistent atrial fibrillation - Moyuru Hirata; Koichi Nagashima; Ryuta Watanabe; Yuji Wakamatsu; Naoto Otsuka; Shu Hirata; Masanaru Sawada; Yuji Saito; Sayaka Kurokawa; Kenta Murotani; Yasuo Okumura (Journal of Arrhythmia)
Abstract Background The role of bepridil in preventing atrial fibrillation (AF) recurrence following ablation for persistent atrial fibrillation (PerAF) remains uncertain, particularly in patients with severe atrial substrates. Methods This retrospective study included 232 consecutive PerAF patients who underwent AF ablation between 2014 and 2019. Among them, 162 received bepridil for 3 months post‐ablation (Bepridil group), while 70 received no antiarrhythmic drugs (No‐AADs group). Baseline characteristics, procedural details, and outcomes were compared. Kaplan–Meier analysis and Cox regression models were used to evaluate AF/atrial tachycardia (AT) recurrence, with bepridil use treated as a time‐dependent covariable. Results The Bepridil group had a higher body mass index (25.1 ± 3.7 vs. 23.8 ± 3.9), a higher prevalence of patients with a LAD >40 mm and a LAV >50 mL (67.9% vs. 47.1%, 64.2% vs. 48.5%, respectively), and lower left atrial appendage flow velocity (37.6 ± 15.0 vs. 42.7 ± 20.5 cm/min). They more frequently underwent intracardiac atrial cardioversion (61.7% vs. 40.0%) and additional extra‐pulmonary vein ablation (35.2% vs. 15.7%), but were less likely to receive balloon‐based ablation (39.5% vs. 62.9%) (p < 0.05 for all comparison). During a median follow‐up of 23.3 months, AF/AT‐free survival at 2 years was comparable between the Bepridil and No‐AADs groups (80.4% vs. 81.7%; p = 0.61). This finding remained consistent after adjusting for baseline characteristics and considering bepridil as a time‐dependent covariable. No bepridil‐related adverse events occurred. Conclusion Bepridil may have a limited role in preventing AF/AT recurrence in PerAF patients, particularly those with severe atrial substrates. However, its overall impact appears to be small, warranting further investigation.